A Decision Support System on Biodrainage for Land Reclamation - J. Dash; A. Sarangi; A.K. Singh (Journal of Soil and Water Conservation, 2022)
A Decision Support System (DSS) on bio-drainage for reclamation of salt affected and waterlogged lands was developed using Visual Basic (VB) protocols. The DSS permits the user to interactively enter input information viz., he area available for plantation, average annual rainfall, initial and desired water table depth, soil type and the plantation type, etc. Based on the input data, the DSS generates a number of scenarios of planting densities, time period of reclaiming the land up to desired water level along with the salt uptake rate. The nested VB programming construct, If...Then...Else was most frequently used as an interpretive algorithm for the generation of alternative decisions for different input data. The operation of the DSS for a hypothetical waterlogged land of 1 ha revealed that Acacia biflora plants at 400 plants/ha planting density would cause a decline of water table by 1 m in 0.40 years; by 2 m in 0.84 years and by 3 m in 1.32 years. With the same planting density and at the sapling stage, the plants would extract 11.48 kg of salts in 6 months. The DSS is flexible to incorporate the information of water and salt uptake rate of a variety of plants. Moreover, inclusion of the salt uptake data of the matured bio drainage species in the DSS protocol con enhance the operability of the DSS for more efficient salinity management of the bio-drained lands.